2006
DOI: 10.3892/or.15.3.533
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of mouse urinary bladder carcinogenesis by fermented brown rice and rice bran

Abstract: Abstract. Fermented brown rice by Aspergillus oryzae (FBRA) has been shown to be a potent anti-carcinogenic compound. Here, we investigated the modifying effects of dietary feeding with a naturally occurring anti-oxidant FBRA on N-butyl-N-(4-hydroxybutyl)-nitrosamine (OH-BBN)-induced urinary bladder carcinogenesis in male ICR mice. Five-week-old male ICR mice were divided into 7 groups, and groups 1-5 were given OH-BBN (500 ppm) in drinking water for 6 weeks starting at 7 weeks of age. Groups 2 and 3 were fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 27 publications
5
28
1
Order By: Relevance
“…A number of studies have shown the chemopreventive effect of fermented brown rice and rice bran (FBRA) on several types of cancer, including colon cancer (12)(13)(14)(15). In contrast to previous findings that FBRA significantly suppressed azoxymethane-induced colorectal carcinogenesis in rats, in the present study, FBRA has no effect on the tumor development of the colon in Apc Min/+ genetic background.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…A number of studies have shown the chemopreventive effect of fermented brown rice and rice bran (FBRA) on several types of cancer, including colon cancer (12)(13)(14)(15). In contrast to previous findings that FBRA significantly suppressed azoxymethane-induced colorectal carcinogenesis in rats, in the present study, FBRA has no effect on the tumor development of the colon in Apc Min/+ genetic background.…”
Section: Discussioncontrasting
confidence: 55%
“…Fermented brown rice and rice bran (FBRA) is a processed food prepared by fermented the brown rice and rice bran with Aspergillus oryzae. In our previous studies, FBRA showed chemopreventive effect against various types of chemically-induced cancer, including colon (12), stomach (13), bladder (14) and esophagus (15) …”
Section: Introductionmentioning
confidence: 99%
“…A brown rice preparation (2.5 or 5% in the diet), obtained by fermentation with Aspergillus oryzae, interfered with azoxymethane-induced formation of aberrant crypt foci and adenocarcinomas in rats (Katayama et al, 2002). Furthermore, fermented brown rice reduced diethylnitrosamine-and phenobarbital-induced hepatocarcinogenesis in rats (Katayama et al, 2003), N-nitrosomethylbenzylamine-induced oesophageal tumorigenesis in rats (Kuno et al, 2004) and bladder carcinogenesis in mice (Kuno et al, 2006). To our knowledge there is no information in the literature on the epidemiology, linking consumption of brown rice or rice bran to colorectal cancer risk in humans, which would complement the available data in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to colonic and gastric cancers, fermented brown rice has demonstrated chemopreventive effects against cancers of the lung, liver, bladder, tongue, and esophagus (28)(29)(30)(31)(32). All of these studies were able to demonstrate that the feeding of fermented brown rice to carcinogen-treated mice significantly decreased the incidence and multiplicity of the tumors in the respective tissues.…”
Section: Introductionmentioning
confidence: 99%